Africa and the West: elements of free-world policy - Rivkin, Arnold (London: Thames and Hudson, 1962)
This book tries to identify crucial problems of African development and their implications for the United States and for the free-world policy generally. It include topics like: the African outlook; Western Europe$1 (Bs changing perspectives and policies; the role of EEC in Africa; the United States outlook; the Israeli outlook; Arms for life; the role of United Nations in Congo; the role of the United Nations in the Trust Territories (Cameroun, Togo, Somalia); advance technologies and stages of growth; and proposal for multilateral aid organisation.s
Includes index
lje 28/09/2018
Loans
Keywords: Economic development; Aid; Africa; Africa; Africa